Secondary battery and manufacturing method thereof
The semi-solid electrode with a carbon layer addresses high resistance and manufacturing complexity in secondary batteries by eliminating binders and simplifying processes, improving energy density and rate characteristics.
Patent Information
- Application Number
- JP2021165046
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2021-10-06
- Publication Date
- 2025-01-29
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Conventional secondary batteries face issues with high electrical resistance due to the presence of binders, complex manufacturing processes, and reduced energy and rate characteristics in semi-solid electrodes, which are not adequately pressed and require additional conductors, increasing interface resistance and electrolyte usage.
The introduction of a semi-solid electrode layer with a carbon layer between the electrode layer and the collector, eliminating the need for binders and simplifying the manufacturing process by omitting pressing steps, thereby reducing interface resistance and electrolyte usage.
This approach enhances energy density and rate characteristics by minimizing interface resistance and electrolyte requirements, while significantly reducing manufacturing complexity and costs.
Smart Images

Figure 2025014073000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a secondary battery, in particular a secondary battery including a semi-solid electrode, and a method for producing the same. [Background technology]
[0002] Conventionally, secondary batteries have been used as power sources for various electronic devices. A secondary battery generally has a structure in which a laminate in which a positive electrode having a positive electrode layer and a negative electrode having a negative electrode layer are alternately laminated with a separator interposed therebetween, and an electrolyte is contained within an exterior body. In addition, as electrodes such as a positive electrode and a negative electrode, a binder-bonded electrode in which an electrode active material, a conductive assistant, and the like are bound by a binder on a current collector is used.
[0003] On the other hand, secondary batteries using so-called semi-solid electrodes having fluidity instead of binder-bonded electrodes are known for the purposes of simplifying and reducing manufacturing costs, reducing inactive components in electrodes and secondary batteries, and improving energy density, charge capacity, and overall performance (e.g., Patent Document 1). [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Special Publication No. 2016-500465 Summary of the Invention [Problem to be solved by the invention]
[0005] The inventors of the present invention have found that the following new problems may arise in conventional secondary batteries.
[0006] (1) In the binder-bonded electrode, the binder is present in a relatively large amount, which hinders the movement of electrons and ions and increases the electrical resistance, resulting in a decrease in rate characteristics.
[0007] (2) A method for producing a secondary battery including a binder-bonded electrode includes, as electrode production steps, a preparation step of preparing an electrode layer-forming coating liquid; a coating step of coating a current collector with the electrode layer-forming coating liquid; a drying step of drying the coated electrode layer; a pressing step of compacting the electrode precursor; a slitting step of cutting the electrode precursor to a desired width; and a cutting step of cutting the electrode precursor to a desired size to form an electrode; and, as assembly steps, a welding step of connecting tabs to the electrodes; a lamination step of laminating the electrodes so that the positive electrodes and negative electrodes are arranged alternately with a separator arranged between them to produce a laminate; a liquid injection step of sandwiching the produced laminate within an exterior body and injecting an electrolyte into the exterior body; a vacuum impregnation step of impregnating the electrodes with the electrolyte while maintaining a vacuum inside the exterior body; an encapsulation step of enclosing the laminate in the exterior body; a charge-discharge step of forming a solid electrolyte interface coating on the surface of the negative electrode active material by an initial charging treatment to form a secondary battery precursor; and an aging step of aging the secondary battery precursor. Such a complicated and lengthy manufacturing process increases the capital investment and manufacturing process costs, raising the manufacturing cost of the secondary battery.
[0008] (3) Semi-solid electrodes can be made much thicker than conventional electrodes, so the ratio of active material to inactive material (i.e., current collector and separator) can be higher in batteries using semi-solid electrodes than in secondary batteries using conventional electrodes. This significantly increases the charge capacity and overall energy density of secondary batteries containing semi-solid electrodes. However, in secondary batteries containing semi-solid electrodes, the semi-solid electrodes do not undergo a pressing process, so the electrode layer and the current collector are not sufficiently pressed together, and the interfacial resistance between the electrode layer and the current collector is likely to be large. This results in a decrease in rate characteristics. In order to sufficiently reduce the interfacial resistance between the electrode layer and the current collector, it may be necessary to add more conductive additive than necessary to the electrode layer. However, because the conductive additive has a high liquid absorbing property, the amount of electrolyte required to impart fluidity to the electrode increases. As a result, the energy density decreases.
[0009] The present invention aims to provide a secondary battery having excellent rate characteristics and sufficiently excellent energy density, and a manufacturing method thereof. The energy density is, for example, a characteristic related to the amount of energy that can be generated from one electrode layer, and specifically, may be a characteristic determined according to the content ratio of the active material in the semi-solid electrode layer. The rate characteristic is, for example, the capacity maintenance rate of the secondary battery when discharged at a high rate (for example, a characteristic related to the discharge capacity at a high rate / discharge capacity at a reference rate).
[0010] Another object of the present invention is to provide a secondary battery that has superior rate characteristics and sufficiently superior energy density and can be produced in fewer production steps, and a method for producing the same. [Means for solving the problem]
[0011] The present invention relates to The present invention includes a semi-solid electrode having a semi-solid electrode layer including an electrode active material, a conductive assistant, and an electrolyte, and a current collector, The semi-solid electrode relates to a secondary battery having a carbon layer between the semi-solid electrode layer and the current collector.
[0012] The present invention also provides The present invention relates to a method for producing the above-mentioned secondary battery, the method comprising the steps of: a preparation step of mixing an electrode active material, a conductive assistant, and an electrolyte to prepare a slurry for an electrode layer; a carbon layer forming step of forming a carbon layer on the current collector; a coating step of coating a slurry for an electrode layer onto a current collector having a carbon layer to form an electrode; a lamination step of laminating the electrodes to form a laminate such that a separator is disposed between the electrodes; An encapsulation step of encapsulating the laminate in an exterior case. Effect of the Invention
[0013] In the secondary battery of the present invention, the interface resistance between the electrode layer and the current collector can be reduced by using a carbon-treated current collector, even in the case of an electrode that does not undergo a pressing process, and therefore the rate characteristics are sufficiently superior. Furthermore, in the secondary battery of the present invention, the amount of conductive assistant added is the minimum amount necessary to ensure the conductivity of the electrode layer, so that the amount of electrolyte to give the electrode fluidity is small, and the energy density can be increased. In the secondary battery of the present invention, the secondary battery manufacturing process can be significantly simplified, so that the capital investment cost and manufacturing process cost can be significantly reduced. The secondary battery of the present invention also has an increased energy density because the amount of electrolyte required to impart fluidity to the electrodes is reduced. The secondary battery of the present invention also has excellent rate characteristics because it does not contain a binder and can achieve low resistance. [Brief description of the drawings]
[0014] [Figure 1] FIG. 1 is an example of a schematic cross-sectional view of a secondary battery according to an embodiment of the present invention, for explaining the mechanism by which the rate characteristics are improved in the secondary battery. [Diagram 2] FIG. 2 is a schematic cross-sectional view of a conventional secondary battery for illustrating the mechanism by which the rate characteristics of the conventional secondary battery decrease. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] [Secondary battery] The present invention provides a secondary battery. In this specification, the term "secondary battery" refers to a battery that can be repeatedly charged and discharged. The term "secondary battery" is not limited to its name, and may also include electrochemical devices such as "electricity storage devices". In this specification, "planar view" refers to a state (top view or bottom view) when an object is viewed from above or below (particularly from above) along the thickness direction (for example, the stacking direction of electrodes and separators). In this specification, "cross-sectional view" refers to a cross-sectional state (cross-sectional view) when viewed from a direction perpendicular to the thickness direction. It should be noted that the various elements shown in the drawings are merely shown diagrammatically for understanding the present invention, and that the dimensional ratio and appearance may differ from the actual objects. The "up-down direction", "left-right direction", and "front-back direction" used directly or indirectly in this specification correspond to the up-down direction, left-right direction, and front-back direction in the drawings, respectively. Unless otherwise specified, the same symbols or symbols indicate the same members or the same meanings. In a preferred embodiment, the vertical downward direction (i.e., the direction in which gravity acts) can be considered to correspond to the "downward direction", and the opposite direction can be considered to correspond to the "upward direction".
[0016] In the present invention, each member constituting a secondary battery is disposed on the positive electrode side and the negative electrode side, respectively, unless otherwise specified. For example, the electrode includes a positive electrode and a negative electrode. Also, for example, the electrode active material (or active material) includes a positive electrode active material and a negative electrode active material. Also, for example, the conductive assistant includes a positive electrode conductive assistant and a negative electrode conductive assistant. Also, for example, the electrolyte includes a positive electrode electrolyte and a negative electrode electrolyte. Note that the positive electrode electrolyte and the negative electrode electrolyte may be electrolytes of the same composition.
[0017] The secondary battery of the present invention will be described in detail below with reference to the drawings. As shown in FIG. 1, the secondary battery 10 of the present invention has a semi-solid electrode 1. The semi-solid electrode of FIG. 1 is a schematic representation of either a semi-solid positive electrode or a semi-solid negative electrode. The semi-solid electrode 1 has a semi-solid electrode layer 7, a current collector 5, and a carbon layer 6 between the semi-solid electrode layer 7 and the current collector 5. The semi-solid electrode layer 7 is usually a layer that contains an electrode active material 2, a conductive assistant 3, and an electrolyte 4, and has fluidity. FIG. 2 shows a conventional secondary battery having a semi-solid electrode 1'. The semi-solid electrode 1' includes a semi-solid electrode layer 7' that contains an active material 2', a conductive assistant 3', and an electrolyte 4', and a current collector 5'. However, unlike FIG. 1, the conventional secondary battery of FIG. 2 does not have a carbon layer 6. The semi-solid electrodes 1 and 1' are also called clay electrodes because they have a semi-solid electrode layer. The conductive assistant 3 does not necessarily have to be contained in both the semi-solid positive electrode and the semi-solid negative electrode. For example, both the positive electrode and the negative electrode may contain the conductive assistant 3, or both may not. For example, the positive electrode may contain the conductive assistant 3 and the negative electrode may not contain the conductive assistant 3. For example, the positive electrode may not contain the conductive assistant 3 and the negative electrode may contain the conductive assistant 3. The conductive assistant 3 is usually contained at least in the positive electrode. FIG. 1 is a cross-sectional view showing a schematic example of a basic structure of a secondary battery according to an embodiment of the present invention.
[0018] In the present invention, both electrodes (i.e., positive and negative electrodes) are usually semi-solid electrodes. Thus, the positive and negative electrodes correspond to a semi-solid positive electrode and a semi-solid negative electrode, respectively. In other words, the secondary battery of the present invention includes a semi-solid positive electrode and a semi-solid negative electrode, and at least one of the semi-solid positive electrode and the semi-solid negative electrode corresponds to a semi-solid electrode. The term "semi-solid electrode" means that the electrode layer (particularly the material) is a mixture of a solid phase and a liquid phase, and the mixture may have the form of, for example, a slurry, a colloidal suspension, an emulsion, a gel, or a micelle or particle suspension. Thus, the electrode layer of the semi-solid electrode (i.e., the semi-solid electrode layer) is specifically composed of a slurry containing an electrode active material (usually solid-phase particles) and an electrolyte (usually liquid phase), and may further contain additives such as a conductive assistant (usually solid-phase particles). Such a semi-solid electrode layer is different from a conventional binder-bound electrode layer and does not contain a binder for binding and / or fixing the electrode active materials to each other. In the present invention, since the electrode (particularly the electrode layer) does not contain such a binder, it is possible to avoid an increase in electrical resistance caused by the binder, and it is possible to achieve a further increase in the capacity of the secondary battery. In the present invention, the semi-solid electrode (particularly the semi-solid electrode layer) does not strictly not contain a binder. The present invention does not prevent the inclusion of a trace amount of binder as an impurity unintentionally mixed into the electrode layer during the manufacturing process, and a supporting base material for supporting the carbon material contained in the carbon layer. From this perspective, the content of the binder contained in the semi-solid electrode (particularly the semi-solid electrode layer) may be 0.1 mass % or less, particularly 0.01 mass % or less, based on the total amount of the semi-solid electrode layer. The content of the binder may be within the above range in each of the semi-solid positive electrode layer or the semi-solid negative electrode layer (particularly the semi-solid positive electrode layer).
[0019] One embodiment of the present invention includes a semi-solid electrode having a semi-solid electrode layer including an electrode active material, a conductive assistant, and an electrolyte, and a current collector, the semi-solid electrode having a carbon layer between the semi-solid electrode layer and the current collector.
[0020] The carbon layer is a layer including a carbon material and a support matrix (hereinafter referred to as the support matrix) for supporting the carbon material. The support matrix is a material that disperses and fixes the carbon material in the matrix, and may be a material included in materials called binders. As the support matrix, for example, a polymer such as a polymer (e.g., so-called plastic or rubber) is used. Due to these characteristics, the carbon layer may be a polymer layer in which the carbon material is dispersed. The carbon layer may be referred to as a carbon coat layer.
[0021] As shown in FIG. 1, the carbon layer 6 is provided between the semi-solid electrode layer 7 and the current collector 5. Specifically, the carbon layer 6 is formed in direct contact with the surface of the current collector 5 and also in direct contact with the semi-solid electrode layer 7. Therefore, the contact frequency between the carbon material in the carbon layer 6 and the current collector 5 becomes relatively high (region indicated by 8 in FIG. 1), and the contact frequency between the semi-solid electrode layer 7 and the carbon material in the carbon layer 6 also becomes relatively high. As a result, the interface resistance between the semi-solid electrode layer and the current collector 5 becomes relatively low, and the rate characteristics become more sufficiently excellent. On the other hand, in the conventional secondary battery 10′, as shown in FIG. 2, the contact frequency between the current collector 5′ and the carbon material in the semi-solid electrode layer 7′ is relatively low (region indicated by 8′ in FIG. 2). Therefore, the interface resistance between the semi-solid electrode layer and the current collector becomes relatively high, and the rate characteristics become poor. Although not shown in FIG. 1, the carbon layer 6 in FIG. 1 also includes a support base material.
[0022] The carbon material is a substance mainly composed of carbon (C). The carbon material may be conductive and is not particularly limited, but may be at least one selected from carbon black such as thermal black, furnace black, channel black, ketjen black, and acetylene black, graphite, carbon nanotubes, and carbon fibers such as vapor-grown carbon fibers. From the viewpoint of further reducing the interface resistance between the electrode layer and the current collector and further improving the rate characteristics, it is preferable to use carbon black as the carbon material. The shape of the carbon material is not particularly limited, and any shape such as spherical, plate, and fiber may be used.
[0023] From the viewpoint of further reducing the interfacial resistance between the electrode layer and the current collector and further improving the rate characteristics, the content of the carbon material contained in the carbon layer is preferably 20% by volume to 60% by volume, more preferably 30% by volume to 55% by volume, even more preferably 35% by volume to 50% by volume, and particularly preferably 35% by volume to 45% by volume, based on the total amount of the carbon layer. The total amount of the carbon layer means the total content of each component (e.g., carbon material and supporting matrix) constituting the carbon layer.
[0024] The content of the carbon material contained in the carbon layer is, for example, a value measured by the following method: It is found by calculating the ratio of the area of the carbon material contained in the carbon layer to the total area of the carbon layer from a cross-sectional image of the carbon layer observed by SEM.
[0025] The average particle size of the carbon material contained in the carbon layer is not particularly limited. For example, when the particle size of the carbon material is measured by a laser diffraction / scattering method, the particle size of the carbon material is preferably 0.01 μm or more and 5 μm or less, more preferably 0.05 μm or more and 4 μm or less, even more preferably 0.1 μm or more and 3 μm or less, and particularly preferably 0.1 μm or more and 1 μm or less, from the viewpoint of further reducing the interfacial resistance between the electrode layer and the current collector and further improving the rate characteristics.
[0026] The support matrix may contain one or more polymers. Examples of the support matrix include polyacrylonitrile, polyvinylidene fluoride, copolymers of vinylidene fluoride and hexafluoropropylene, polytetrafluoroethylene, polyhexafluoropropylene, polyethylene oxide, polypropylene oxide, polyphosphazene, polysiloxane, polyvinyl acetate, polyvinyl alcohol, polymethyl methacrylate, polyacrylic acid, polymethacrylic acid, CMC, styrene-butadiene rubber, nitrile-butadiene rubber, polystyrene and / or polycarbonate, or other polymers, or mixtures thereof. From the viewpoint of further reducing the interfacial resistance between the electrode layer and the current collector and further improving the rate characteristics, the support matrix preferably contains CMC and styrene-butadiene rubber.
[0027] From the viewpoint of further reducing the interfacial resistance between the electrode layer and the current collector and further improving the rate characteristics, the content of the supporting material in the carbon layer is preferably 30 vol. % or more and 90 vol. % or less, more preferably 40 vol. % or more and 80 vol. % or less, even more preferably 50 vol. % or more and 70 vol. % or less, and particularly preferably 55 vol. % or more and 65 vol. % or less, relative to the total amount of the carbon layer.
[0028] When the supporting matrix contained in the carbon layer contains two or more types of polymers, the content of the supporting matrix relative to the total amount of the carbon layer may be the total value of the contents (volume %) of the two or more types of polymers relative to the total amount of the carbon layer. When the supporting matrix contains two or more types of polymers, the content ratio of each of the two or more types of polymers contained in the supporting matrix is not particularly limited. From the viewpoint of further reducing the interface resistance between the electrode layer and the current collector and further improving the rate characteristics, it is preferable that the two or more types of polymers contained in the supporting matrix are contained in equal amounts.
[0029] The carbon layer may be insoluble in the electrolyte contained in the semi-solid electrode. In other words, the support matrix contained in the carbon layer may not have solubility in the solvent of the electrolyte contained in the semi-solid electrode layer. "Not soluble" means that, for example, at 20°C ± 5, the support matrix dissolves in 1 mL of the solvent of the electrolyte contained in the semi-solid electrode layer in an amount of 0.001 g or less. From the viewpoint of further reducing the interface resistance between the electrode layer and the current collector and further improving the rate characteristics, the support matrix dissolves in 1 mL of the solvent of the electrolyte contained in the semi-solid electrode layer in an amount of 0.0001 g or less at 20°C ± 5, and particularly preferably 0.00001 g or less.
[0030] From the viewpoint of further reducing the interfacial resistance between the electrode layer and the current collector and further improving the rate characteristics, the thickness of the carbon layer is preferably 0.1 μm to 10 μm, more preferably 0.3 μm to 8 μm, even more preferably 0.5 μm to 5 μm, and particularly preferably 0.75 μm to 2 μm. The thickness of the carbon layer may be measured, for example, by measuring the length from a SEM image of a cross section.
[0031] The carbon layer is provided in the semi-solid electrode. Specifically, the carbon layer is provided between the semi-solid electrode layer and the current collector. In other words, the carbon layer is formed on the current collector. From the viewpoint of further reducing the interface resistance between the electrode layer and the current collector and further improving the rate characteristics, it is preferable that the carbon layer is formed so as to be in close contact with the current collector.
[0032] The carbon layer does not necessarily have to be provided on both the semi-solid positive electrode and the semi-solid negative electrode, but may be provided on at least one of these electrodes (particularly the positive electrode). For example, the carbon layer may be provided on each of the positive electrode and the negative electrode. For example, the carbon layer may be provided on the positive electrode and the carbon layer may not be provided on the negative electrode. For example, the carbon layer may not be provided on the positive electrode and the carbon layer may be provided on the negative electrode. The carbon layer is usually provided at least on the positive electrode. For example, when the carbon layer is provided on the positive electrode, the "semi-solid electrode layer", the "current collector", and the "electrolyte" correspond to the "semi-solid positive electrode layer", the "positive electrode current collector", and the "positive electrode electrolyte", respectively. For example, when the carbon layer is provided on the negative electrode, the "semi-solid electrode layer", the "current collector", and the "electrolyte" correspond to the "semi-solid negative electrode layer", the "negative electrode current collector", and the "negative electrode electrolyte", respectively.
[0033] The method for providing the carbon layer on the current collector is not particularly limited. For example, a slurry in which the carbon material and the supporting base material are dispersed (the supporting base material may be dissolved in the slurry) may be applied to the current collector and dried to provide the carbon layer on the current collector. The method for applying the slurry to the current collector is not particularly limited, and may be applied, for example, by a doctor blade method.
[0034] In the secondary battery of the present invention, since a carbon layer is provided between the electrode layer and the current collector, the interface resistance between the electrode layer and the current collector can be reduced. Therefore, even when the conductivity of the electrode layer is low and the interface resistance between the electrode layer and the current collector is more rate-determining, the secondary battery of the present invention has a low interface resistance between the electrode layer and the current collector, so that the rate characteristics can be improved. That is, even if the secondary battery of the present invention has an electrode layer conductivity that does not allow conventional secondary batteries to exhibit sufficient rate characteristics, the secondary battery of the present invention has a lower interface resistance between the electrode layer and the current collector, so that the rate characteristics are sufficiently superior. In other words, the secondary battery of the present invention exhibits a rate characteristic that is sufficiently superior to that of conventional secondary batteries when the conductivity of the electrode layer is lower. For example, the secondary battery of the present invention has a semi-solid positive electrode layer conductivity of 5.0×10 -2S / cm, preferably less than 3.5×10 -2 S / cm, more preferably less than 1.0×10 -2 S / cm, more preferably less than 0.5×10 -2 S / cm, preferably less than 0.25×10 -2 S / cm or less, especially preferably 0.15×10 -2 For example, the secondary battery of the present invention may have a semi-solid negative electrode layer having a conductivity of less than 5.0×10 S / cm. -2 S / cm, preferably less than 3.5×10 -2 S / cm, more preferably less than 1.0×10 -2 S / cm, more preferably less than 0.5×10 -2 S / cm, preferably less than 0.25×10 -2 S / cm or less, especially preferably 0.15×10 -2 It may be less than S / cm.
[0035] When the conductivity of the electrode layer is low, the interfacial resistance between the electrode layer and the current collector becomes more rate-determining, and the decrease in rate characteristics becomes more significant. The conductivity of the electrode layer is measured, for example, by the following method. A dielectric measurement tool is attached to a rheometer (Discovery HR-1) manufactured by TA Instruments, and an impedance analyzer EC-Lab-BI-001 is connected to the tool to measure the volume resistivity of the electrode layer, and the reciprocal of the measurement is taken as the conductivity. The measurement was performed by changing the gap to 500, 300, and 100 μm with the rheometer, and multiplying the slope (Ω / cm) of the resistance value and gap obtained at 100 kHz by the area (cm) of the measurement tool plate. 2 ) was multiplied.
[0036] The conductivity of the electrode layer can be controlled by adjusting the amount of the conductive assistant contained in the electrode layer. For example, by reducing the amount of the conductive assistant contained in the electrode layer, the conductivity of the electrode layer can be lowered. On the other hand, by increasing the amount of the conductive assistant contained in the electrode layer, the conductivity of the electrode layer can be increased.
[0037] The positive electrode active material contained in the positive electrode and the negative electrode active material contained in the negative electrode are materials directly involved in the transfer of electrons in the secondary battery, and are the main materials of the positive and negative electrodes that are responsible for charging and discharging, i.e., the battery reaction. More specifically, ions are brought to the electrolyte due to the "positive electrode active material contained in the positive electrode" and the "negative electrode active material contained in the negative electrode", and these ions move between the positive electrode and the negative electrode to transfer electrons and charge and discharge. Such mediator ions are not particularly limited as long as they can be charged and discharged, and examples thereof include lithium ions or sodium ions (particularly lithium ions). The positive electrode and the negative electrode may be electrodes that can particularly absorb and release lithium ions. In other words, the secondary battery of the present invention may be a secondary battery in which lithium ions move between the positive electrode active material and the negative electrode active material via the electrolyte to charge and discharge the battery. When lithium ions are involved in charging and discharging, the secondary battery of the present invention corresponds to a so-called "lithium ion battery".
[0038] The positive electrode active material of the positive electrode is preferably made of, for example, granular material. Furthermore, it is also preferable that a conductive assistant is contained in the positive electrode (particularly the positive electrode layer) in order to facilitate the transfer of electrons that promote the battery reaction. Similarly, the negative electrode active material of the negative electrode is preferably made of, for example, granular material, and a conductive assistant may be contained in the negative electrode (particularly the negative electrode layer) in order to facilitate the transfer of electrons that promote the battery reaction. In this way, since a plurality of components are contained, the positive electrode layer and the negative electrode layer can also be called "positive electrode composite layer" and "negative electrode composite layer", respectively.
[0039] As described above, the semi-solid electrode layer includes an electrode active material, a conductive assistant, and an electrolyte. Since the semi-solid electrode does not undergo a pressing process, it may be necessary to add more conductive assistant than necessary to the electrode layer in order to more sufficiently reduce the interfacial resistance between the semi-solid electrode layer and the current collector. If the amount of conductive assistant is increased, the amount of electrolyte required to impart fluidity to the semi-solid electrode layer will increase because the conductive assistant has high liquid catching ability. If the amount of conductive assistant in the electrode layer is increased and the amount of electrolyte is also increased, the amount of active material in the electrode layer will relatively decrease, and the energy density will decrease further. The energy density here means the active material ratio in the electrode layer. On the other hand, if the amount of conductive assistant contained in the electrode layer is reduced, the amount of electrolyte required to impart fluidity to the semi-solid electrode layer will decrease. If the amount of conductive assistant in the electrode layer is reduced and the amount of electrolyte is also reduced, the amount of active material will relatively increase, and the energy density will increase further. The secondary battery of the present invention has a carbon layer between the electrode layer and the current collector, and therefore has low interfacial resistance between the semi-solid electrode layer and the current collector, and is superior in rate characteristics, even when the amount of conductive assistant is relatively small. Therefore, the secondary battery of the present invention can reduce the amount of conductive assistant in the electrode layer while maintaining superior rate characteristics, and can also reduce the amount of electrolyte required to impart fluidity. In addition, since the amounts of conductive assistant and electrolyte can be relatively reduced, the secondary battery of the present invention can relatively increase the amount of active material in the electrode layer, and can further increase the energy density.
[0040] The positive electrode active material is preferably a material that contributes to the absorption and release of lithium ions. From this viewpoint, the positive electrode active material is preferably, for example, a lithium-containing composite oxide. More specifically, the positive electrode active material is preferably a lithium transition metal composite oxide containing lithium and at least one transition metal selected from the group consisting of cobalt, nickel, manganese, and iron. That is, in the positive electrode layer of the secondary battery according to the present invention, such a lithium transition metal composite oxide is preferably contained as the positive electrode active material. For example, the positive electrode active material may be lithium cobalt oxide, lithium nickel oxide, lithium manganate, lithium iron phosphate, or a material in which a part of the transition metal is replaced with another metal. Such a positive electrode active material may be contained as a single type, or may be contained in a combination of two or more types. In a more preferred embodiment, the positive electrode active material contained in the positive electrode (particularly the positive electrode layer) is lithium cobalt oxide.
[0041] The average particle size of the positive electrode active material is not particularly limited and may be, for example, 1 μm or more and 100 μm or less, particularly 1 μm or more and 50 μm or less. From the viewpoints of further improving the energy density, further reducing the interfacial resistance between the electrode layer and the current collector, and further improving the rate characteristics, the average particle size is preferably 1 μm or more and 30 μm or less, and more preferably 10 μm or more and 20 μm or less.
[0042] The average particle size of the positive electrode active material is the particle size D50 at which the cumulative particle volume from the small particle size side reaches 50% of the total particle volume in the particle size distribution determined by a laser diffraction / scattering method.
[0043] The content of the positive electrode active material is usually 50% by mass or more and 90% by mass or less with respect to the total amount of the positive electrode layer, and from the viewpoint of further improving the energy density, further reducing the interfacial resistance between the electrode layer and the current collector, and further improving the rate characteristics, it is preferably 55% by mass or more and 90% by mass or less, more preferably 60% by mass or more and 90% by mass or less, even more preferably 70% by mass or more and 90% by mass or less, and particularly preferably 80% by mass or more and 90% by mass or less. The total amount of the positive electrode layer means the total content of each component (e.g., positive electrode active material, conductive assistant, electrolyte) constituting the positive electrode layer excluding the current collector.
[0044] The content of the positive electrode active material in the positive electrode layer may be measured, for example, by weighing a predetermined amount of the positive electrode layer, quantifying the amount of metal ions contained in the positive electrode active material by inductively coupled plasma mass spectrometry (ICP-MS), and converting the amount into the content of the positive electrode active material.
[0045] The conductive assistant that can be contained in the positive electrode (i.e., the positive electrode conductive assistant) is not particularly limited, but may be at least one selected from carbon black such as thermal black, furnace black, channel black, ketjen black, and acetylene black, carbon fibers such as graphite, carbon nanotubes, and vapor-grown carbon fibers, metal powders such as copper, nickel, aluminum, and silver, and polyphenylene derivatives. In a more preferred embodiment, the conductive assistant of the positive electrode layer is carbon black. In a further preferred embodiment, the positive electrode active material and conductive assistant of the positive electrode layer are a combination of lithium cobalt oxide and carbon black.
[0046] The average particle size of the conductive assistant contained in the positive electrode (particularly the positive electrode layer) is not particularly limited and may be, for example, 0.1 μm or more and 20 μm or less, particularly 0.1 μm or more and 10 μm or less. From the viewpoint of further reducing the interfacial resistance between the electrode layer and the current collector and further improving the rate characteristics, it is preferably 0.5 μm or more and 8 μm or less, more preferably 1 μm or more and 5 μm or less.
[0047] The average particle size of the conductive additive contained in the positive electrode (particularly the positive electrode layer) is the particle size D50 at which the cumulative particle volume from the small particle size side reaches 50% of the total particle volume in the particle size distribution determined by a laser diffraction / scattering method.
[0048] The content of the conductive assistant contained in the positive electrode (particularly the positive electrode layer) is usually 0.1 mass % or more and 10 mass % or less, relative to the total amount of the positive electrode layer, and from the viewpoints of further improving the energy density, further reducing the interfacial resistance between the electrode layer and the current collector, and further improving the rate characteristics, the content is preferably 0.5 mass % or more and 5 mass % or less, more preferably 0.5 mass % or more and 3.5 mass % or less, and particularly preferably 0.5 mass % or more and 2 mass % or less.
[0049] The content of the conductive assistant in the positive electrode layer may be measured, for example, by thermogravimetric differential thermal analysis (TG-DTA).
[0050] The negative electrode active material is preferably a material that contributes to the absorption and release of lithium ions. From this point of view, the negative electrode active material is preferably, for example, various carbon materials, oxides, or lithium alloys. Examples of various carbon materials for the negative electrode active material include graphite (natural graphite, artificial graphite), hard carbon, soft carbon, and diamond-like carbon. In particular, graphite is preferable because of its high electronic conductivity. Examples of oxides for the negative electrode active material include at least one selected from the group consisting of silicon oxide, tin oxide, indium oxide, zinc oxide, and lithium oxide. The lithium alloy for the negative electrode active material may be any metal that can form an alloy with lithium, and may be, for example, a binary, ternary, or more alloy of lithium and a metal such as Al, Si, Pb, Sn, In, Bi, Ag, Ba, Ca, Hg, Pd, Pt, Te, Zn, or La. It is preferable that such oxides have an amorphous structure. This is because deterioration caused by non-uniformity such as grain boundaries or defects is less likely to occur. In a more preferred embodiment, the negative electrode active material of the negative electrode is artificial graphite.
[0051] The average particle size of the negative electrode active material is not particularly limited and may be, for example, 0.5 μm or more and 50 μm or less, particularly 1 μm or more and 40 μm or less. From the viewpoints of further improving the energy density, further reducing the interfacial resistance between the electrode layer and the current collector, and further improving the rate characteristics, it is preferably 2 μm or more and 30 μm or less, more preferably 5 μm or more and 20 μm or less.
[0052] The average particle size of the negative electrode active material is the particle size D50 at which the cumulative particle volume from the small particle size side reaches 50% of the total particle volume in the particle size distribution determined by a laser diffraction / scattering method.
[0053] The content of the negative electrode active material is usually 10% by mass or more and 90% by mass or less with respect to the total amount of the negative electrode layer, and from the viewpoint of further improving the energy density, further reducing the interfacial resistance between the electrode layer and the current collector, and further improving the rate characteristics, it is preferably 30% by mass or more and 90% by mass or less, more preferably 50% by mass or more and 90% by mass or less, more preferably 60% by mass or more and 90% by mass or less, still more preferably 70% by mass or more and 90% by mass or less, and particularly preferably 80% by mass or more and 90% by mass or less. The total amount of the negative electrode layer means the total content of each component constituting the negative electrode layer excluding the current collector (for example, the negative electrode active material, the conductive assistant, and the electrolyte).
[0054] The conductive assistant that may be contained in the negative electrode (i.e., negative electrode conductive assistant) is not particularly limited, but may include at least one selected from carbon black such as thermal black, furnace black, channel black, ketjen black, and acetylene black; carbon fibers such as carbon nanotubes and vapor-grown carbon fibers; metal powders such as copper, nickel, aluminum, and silver; and polyphenylene derivatives.
[0055] The average particle size of the conductive assistant contained in the negative electrode (particularly the negative electrode layer) is not particularly limited and may be, for example, 0.1 μm or more and 20 μm or less, particularly 0.1 μm or more and 10 μm or less. From the viewpoint of further reducing the interfacial resistance between the electrode layer and the current collector and further improving the rate characteristics, it is preferably 0.5 μm or more and 8 μm or less, more preferably 1 μm or more and 5 μm or less.
[0056] The average particle size of the conductive additive contained in the negative electrode (particularly the negative electrode layer) is the particle size D50 at which the accumulated particle volume from the small particle size side reaches 50% of the total particle volume in the particle size distribution determined by a laser diffraction / scattering method.
[0057] The content of the conductive assistant contained in the negative electrode (particularly the negative electrode layer) is usually 0.1% by mass or more and 10% by mass or less with respect to the total amount of the negative electrode layer, and from the viewpoint of further improving the energy density, further reducing the interfacial resistance between the electrode layer and the current collector, and further improving the rate characteristics, it is preferably 0.1% by mass or more and 2% by mass or less, more preferably 0% by mass or more and 2% by mass or less, and even more preferably 0% by mass. The content of the conductive assistant contained in the negative electrode (particularly the negative electrode layer) being 0% by mass means that the negative electrode (particularly the negative electrode layer) does not contain the conductive assistant.
[0058] The electrolyte contained in the positive electrode and the electrolyte contained in the negative electrode usually have the same composition.
[0059] The electrolyte aids the movement of metal ions released from the electrode active materials (positive and negative active materials). The electrolyte may be a "non-aqueous" electrolyte such as an organic electrolyte or an organic solvent, or an "aqueous" electrolyte containing water. The secondary battery of the present invention is preferably a non-aqueous electrolyte secondary battery using an electrolyte containing a "non-aqueous" solvent and a solute as the electrolyte. The electrolyte may be in the form of a liquid or gel (note that in this specification, a "liquid" non-aqueous electrolyte is also referred to as a "nonaqueous electrolyte").
[0060] A specific solvent for the non-aqueous electrolyte is not particularly limited, and preferably contains at least a carbonate. Such carbonate may be a cyclic carbonate and / or a chain carbonate. Although not particularly limited, the cyclic carbonate may be at least one selected from the group consisting of propylene carbonate (PC), ethylene carbonate (EC), butylene carbonate (BC) and vinylene carbonate (VC). The chain carbonate may be at least one selected from the group consisting of dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC) and dipropyl carbonate (DPC). In one preferred embodiment, a combination of a cyclic carbonate and a chain carbonate is used as the non-aqueous electrolyte, for example, a mixture of ethylene carbonate and ethyl methyl carbonate is used.
[0061] As a specific solute of the non-aqueous electrolyte, for example, Li salts such as LiPF6 and LiBF4 are preferably used. In a preferred embodiment, LiPF6 is used. The concentration of the solute in the electrolyte is not particularly limited, and may be, for example, 0.1M or more and 10M or less, particularly 0.5M or more and 3M or less. M is mol / L.
[0062] The content of the electrolyte in the semi-solid electrode layer affects the fluidity of the semi-solid electrode layer. For example, if the content of the electrolyte in the semi-solid electrode is increased, the fluidity of the semi-solid electrode layer is increased. On the other hand, if the content of the electrolyte in the semi-solid electrode is decreased, the fluidity of the semi-solid electrode layer is decreased. If the content of the electrolyte contained in the semi-solid electrode layer is increased relative to the total amount of the semi-solid electrode layer, the content of the active material contained in the semi-solid electrode layer is relatively decreased, and the energy density is decreased. On the other hand, if the content of the electrolyte contained in the semi-solid electrode layer is decreased relative to the total amount of the semi-solid electrode layer, the content of the active material contained in the semi-solid electrode layer is relatively increased, and the energy density is increased. The content of the electrolyte in the positive electrode (particularly the positive electrode layer) and the negative electrode (particularly the negative electrode layer) is preferably 30% by volume or more and 70% by volume or less, more preferably 33% by volume or more and 67% by volume or less, more preferably 40% by volume or more and 60% by volume or less, and particularly preferably 45% by volume or more and 55% by volume or less, based on the total amount of the positive electrode layer, from the viewpoint of further improving the energy density, further reducing the interfacial resistance between the electrode layer and the current collector, and further improving the rate characteristics. Also, for example, the content of the electrolyte in the negative electrode (particularly the negative electrode layer) is preferably 30% by volume or more and 70% by volume or less, more preferably 33% by volume or more and 67% by volume or less, more preferably 40% by volume or more and 60% by volume or less, and particularly preferably 45% by volume or more and 55% by volume or less, based on the total amount of the negative electrode layer.
[0063] The thickness of the electrode layer is not particularly limited and may be appropriately selected according to the desired battery capacity. The thickness of the electrode layer (particularly the thickness of the electrode layer per one main surface (one side) of the current collector described later) is, for example, such a thickness that the capacity per electrode area on one side in the secondary battery of the present invention falls within the range described later, and is usually 80 μm or more, particularly 150 μm or more and 500 μm or less. The thickness of the electrode layer includes the thickness of the positive electrode layer and the thickness of the negative electrode layer, and each may be selected independently. The thickness of the electrode layer is the average value of the thicknesses at any 50 points in the completed secondary battery.
[0064] An electrode (particularly a semi-solid electrode) is usually provided with an electrode layer (particularly a semi-solid electrode layer) on at least one side (preferably both sides) of a current collector. The constituent material of the current collector is not particularly limited as long as it has electrical conductivity, and may be, for example, one metal selected from the group consisting of copper, aluminum, stainless steel, etc., or an alloy containing two or more metals. The current collector of the positive electrode (i.e., the positive electrode current collector) is preferably made of aluminum from the viewpoint of further reducing the interface resistance between the electrode layer and the current collector and further improving the rate characteristics. The current collector of the negative electrode (i.e., the negative electrode current collector) is preferably made of copper from the viewpoint of further reducing the interface resistance between the electrode layer and the current collector and further improving the rate characteristics.
[0065] There are no particular limitations on the thickness of the positive electrode and negative electrode current collectors, and they may each independently be, for example, from 1 μm to 300 μm, particularly from 1 μm to 100 μm.
[0066] The secondary battery of the present invention is usually enclosed in an exterior body. The exterior body may be a flexible pouch (soft bag) or a hard case (hard housing). From the viewpoint of further reducing the interface resistance between the electrode layer and the current collector and further improving the rate characteristics, the exterior body is preferably a flexible pouch.
[0067] When the exterior body is a flexible pouch, the flexible pouch is usually formed from a laminate film, and the seal part is formed by heat-sealing the periphery. The laminate film is generally a film in which a metal foil and a polymer film are laminated, and specifically, a three-layer structure consisting of an outer layer polymer film / metal foil / inner layer polymer film is exemplified. The outer layer polymer film is for preventing damage to the metal foil due to permeation of moisture and the like and contact, and polymers such as polyamide and polyester can be suitably used. The metal foil is for preventing permeation of moisture and gas, and foils such as copper, aluminum, and stainless steel can be suitably used. The inner layer polymer film is for protecting the metal foil from the electrolyte stored inside and for melt sealing during heat sealing, and polyolefin or acid-modified polyolefin can be suitably used. The thickness of the laminate film is not particularly limited, and is preferably 1 μm or more and 1 mm or less. For example, in the case of a secondary battery having a rectangular shape in plan view, the exterior body is usually heat-sealed at its periphery in plan view. Specifically, when the exterior body is made of two rectangular exterior body materials, the exterior body is usually heat-sealed at its four sides in plan view, and when the exterior body is made of one rectangular exterior body material, one of the four sides in plan view is usually formed by folding back the exterior body material.
[0068] When the exterior body is a hard case, the hard case is usually formed from a metal plate, and the sealing portion is formed by irradiating the peripheral portion with a laser. The metal plate is generally made of a metal material such as aluminum, nickel, iron, copper, or stainless steel. The thickness of the metal plate is not particularly limited, and is preferably, for example, 1 μm or more and 1 mm or less. The sealing of the metal plates may be achieved by irradiating the overlapping portion of the peripheral portion with a laser.
[0069] The secondary battery of the present invention is effective in increasing the capacity. Since the electrode layer is a semi-solid electrode layer and has fluidity, the thickness of the electrode layer can be stably and easily increased simply by increasing the amount of the electrode layer injected. From this viewpoint, the capacity per electrode area on one side of the secondary battery of the present invention is preferably 4 mAh / cm. 2 More preferably, 5 mAh / cm 2 More than 20mAh / cm 2 The capacity per electrode area may be the capacity per collector area since the electrode layer in the present invention is a semi-solid electrode layer. The capacity per electrode area of the positive electrode and the negative electrode may be independently within the above range. When the electrode layer is provided on both sides of the collector, the capacity per electrode area is the capacity per one side. The capacity per electrode area of the secondary battery can be obtained, for example, by dividing the capacity of the secondary battery obtained by 0.2 CA discharge by the electrode area.
[0070] The capacity per electrode area in the secondary battery of the present invention may be the active material capacity per electrode area. The capacity per electrode area may be controlled, for example, by adjusting the amount of slurry containing the active material injected into the electrode. Specifically, the capacity per electrode area may be controlled by adjusting the amount of slurry containing the active material injected into the electrode so as to obtain a predetermined active material capacity per electrode area. The capacity per electrode area includes both the positive electrode and the negative electrode, and the capacity per area of the positive electrode and the negative electrode can be controlled by the same method as the above control method.
[0071] The secondary battery of the present invention may further have a protective layer (not shown) on the outer surface of the exterior body.
[0072] [Secondary battery manufacturing method] The secondary battery 10 of the present invention can be manufactured by a method including the following steps: a preparation step of mixing an electrode active material, a conductive assistant, and an electrolyte to prepare a slurry for electrode layers (i.e., a slurry for a positive electrode layer and a slurry for a negative electrode layer); a carbon layer forming step of forming a carbon layer on the current collector; A coating process of coating a slurry for electrode layers onto a current collector having a carbon layer to form electrodes (i.e., positive and negative electrodes); A lamination step of laminating the electrodes to form a laminate such that a separator is disposed between the electrodes (i.e., between the positive electrode and the negative electrode); and An encapsulation step of encapsulating the laminate in an exterior case.
[0073] The method for producing a secondary battery of the present invention may usually include the following steps immediately after the coating step: A welding process in which a tab is welded to an electrode.
[0074] The method for producing a secondary battery of the present invention may further include, after the encapsulating step, the following steps in sequence: A charge-discharge process in which a solid electrolyte interfacial coating is formed on the surface of the negative electrode active material by an initial charging process to form a secondary battery precursor; and An aging step of aging the secondary battery precursor.
[0075] In the preparation step, specifically, a positive electrode active material, a conductive assistant, an electrolyte, and desired additives are mixed and dispersed to prepare a positive electrode layer slurry, and a negative electrode active material, an electrolyte, and, if desired, a conductive assistant are mixed and dispersed to prepare a negative electrode layer slurry.
[0076] In the carbon layer forming step, more specifically, a support base material having a carbon material dispersed therein is applied to the positive electrode current collector and dried to form a carbon layer on the positive electrode current collector.
[0077] In the coating step, specifically, the positive electrode layer slurry is coated on a positive electrode current collector having a carbon layer to form a positive electrode, and the negative electrode layer slurry is coated on a negative electrode current collector to form a negative electrode. In forming the positive electrode and the negative electrode, the electrode layer slurry is coated independently on at least one surface (preferably both surfaces) of the current collector.
[0078] Then, a welding step may be performed. In the welding step, specifically, a positive electrode tab is welded to the positive electrode. Also, a negative electrode tab is welded to the negative electrode. The material constituting the positive electrode tab and the negative electrode tab is not particularly limited as long as it has electrical conductivity, and may be selected from, for example, materials similar to those constituting the current collector. The positive electrode tab is preferably made of aluminum from the viewpoint of further reducing the interface resistance between the electrode layer and the current collector and further improving the rate characteristics. The negative electrode tab is preferably made of copper from the viewpoint of further reducing the interface resistance between the electrode layer and the current collector and further improving the rate characteristics. The welding step may be performed before (particularly immediately before) the coating step.
[0079] In the lamination step, specifically, positive and negative electrodes are laminated so that the positive and negative electrodes are alternately arranged with a separator disposed therebetween to produce a laminate. The laminate is then sandwiched between exterior body materials. The sandwiching is not particularly limited as long as exterior bodies are arranged at the top and bottom of the laminate in a plan view, and may be achieved, for example, by the following method (i) or (ii): Method (i) sandwiching the laminate between two sheets of exterior material; Method (ii) The laminate is housed in a bag-shaped exterior body having an opening on one side in a plan view, the bag-shaped exterior body having been formed in advance by sealing. In the method (i), instead of the two sheets of exterior body material, one continuous sheet of exterior body material may be folded back.
[0080] In the encapsulation step, more specifically, the overlapping portion at the periphery of the exterior body material is sealed, and the inside of the exterior body is evacuated. In the sandwiching step, when method (i) is employed, the inside of the exterior body is evacuated while the periphery of the exterior body material is sealed at the overlapping portion. When method (ii) is employed, the inside of the exterior body is evacuated while the opening of the bag-shaped exterior body is sealed at the overlapping portion. The overlapping portion refers to the overlapping portion between the exterior body materials.
[0081] Subsequently, a charge / discharge step and an aging step may be performed. In the charge / discharge process, specifically, an initial charge treatment forms a solid electrolyte interface coating (hereinafter, referred to as an "SEI coating") on the surface of the negative electrode active material.
[0082] The initial charging process is a first charging process performed for the purpose of forming an SEI film on the surface of the negative electrode active material, and is also called a conditioning process or a formation process. The SEI film is formed by the reductive decomposition of an additive contained in the electrolyte on the surface of the negative electrode active material in this process, and prevents further decomposition of the additive on the surface of the negative electrode active material during use as a secondary battery. The SEI film usually contains one or more substances selected from the group consisting of LiF, Li2CO3, LiOH, and LiOCOOR (R represents a monovalent organic group, for example, an alkyl group). By forming such an SEI film more uniformly on the surface of the negative electrode active material, decomposition of the electrolyte components in the secondary battery can be prevented, and the capacity stabilization and long life of the secondary battery can be achieved.
[0083] In the initial charging process, charging may be performed at least once. Usually, charging and discharging are performed one or more times. One charging and discharging includes one charging and one subsequent discharging. When charging and discharging are performed two or more times, the charging and discharging are repeated the corresponding number of times. The number of charging and discharging performed in this process is usually from one to three.
[0084] The charging method may be a constant current charging method or a constant voltage charging method, or a combination of these. For example, constant voltage charging and constant voltage charging may be repeated during one charging. The charging conditions are not particularly limited as long as the SEI coating is formed. From the viewpoint of further improving the uniformity of the thickness of the SEI coating, it is preferable to perform constant current charging and then constant voltage charging.
[0085] The discharge method may be a constant current discharge method or a constant voltage discharge method, or a combination of these. The discharge conditions are not particularly limited as long as the SEI film is formed. From the viewpoint of further improving the uniformity of the thickness of the SEI film, it is preferable to perform constant current discharge.
[0086] In the initial charging process, the secondary battery is usually maintained at a temperature within the range of 25°C to 100°C, preferably within the range of 35°C to 90°C, and more preferably within the range of 40°C to 85°C.
[0087] In the aging process, more specifically, the SEI film is stabilized by a stabilization treatment, which is a treatment for stabilizing the SEI film by leaving the secondary battery after the initial charging treatment in an open circuit state.
[0088] The temperature of the secondary battery in the stabilization treatment is not particularly limited, and may be maintained within a range of, for example, 15° C. or more and 80° C. or less. From the viewpoint of further stabilizing the SEI coating, the secondary battery is preferably maintained at a temperature within a range of 20° C. or more and 75° C. or less, and more preferably at a temperature within a range of 25° C. or more and 70° C. or less. In detail, the temperature can be maintained within the above range by leaving the secondary battery in a space set at a constant temperature.
[0089] The time for which the material is left in the stabilization treatment is not particularly limited as long as the stabilization of the SEI coating is promoted, and is usually from 10 minutes to 30 days. From the viewpoint of further stabilizing the SEI coating, the time is preferably within the range of from 30 minutes to 14 days, and more preferably within the range of from 1 hour to 7 days.
[0090] The manufacturing method of the secondary battery according to the present invention only includes a mixing step, a carbon layer forming step, and a coating step as electrode manufacturing steps, and only includes a welding step, a lamination step, an encapsulation step, a charge / discharge step, and an aging step as assembly steps.
[0091] On the other hand, a conventional method for producing a secondary battery including a binder-bonded electrode layer includes, as electrode production steps, a preparation step of preparing an electrode layer-forming coating liquid; a coating step of coating a current collector with the electrode layer-forming coating liquid; a drying step of drying the applied electrode layer-forming coating liquid; a pressing step of compacting the electrode layer; a slitting step of cutting the electrode to a desired width; and a cutting step of cutting the electrode cut to the desired width into a desired shape and size to obtain an electrode, and includes, as assembly steps, a welding step of welding a tab to the electrode; a lamination step of laminating the electrodes so that the positive and negative electrodes constituting the electrode are arranged alternately with a separator arranged between them to produce a laminate; a liquid injection step of sandwiching the produced laminate within an outer casing and injecting an electrolyte into the outer casing; an impregnation step of impregnating the electrodes with the electrolyte under vacuum; and an enclosure step of enclosing the laminate in the outer casing; a charge / discharge step of forming a solid electrolyte interface film on the surface of the negative electrode active material by an initial charging treatment to form a secondary battery precursor; and an aging step of aging the secondary battery precursor. Therefore, in the method for producing a secondary battery according to the present invention, both the electrode production process and the assembly process are greatly simplified, making it possible to achieve a dramatic reduction in capital investment and manufacturing process costs. EXAMPLES
[0092] <Secondary battery manufacturing> (Example 1: Semi-solid electrode type secondary battery) Positive electrode preparation A 1 μm thick carbon layer (composition: carbon black: CMC: SBR = 40:30:30 (vol%)) was formed in advance on the surface of the Al foil to which the positive electrode layer slurry was applied. In detail, the carbon layer on the Al foil surface was obtained by dispersing carbon black with an average particle size of 0.6 μm, CMC, and SBR in water at a ratio of 40:30:30 (vol%), applying the dispersion to a thickness of 1 μm on the surface of the Al foil using a die coater, and drying it. Lithium cobalt oxide (LCO) with an average particle size of 15 μm was used as the positive electrode active material, carbon black with an average particle size of 2.8 μm was used as the conductive additive, and a solution of 1M LiPF6 was used as the electrolyte in a mixed solvent (EC:EMC=25:75 vol) was prepared and dispersed in a weight ratio of 68:3:29 to obtain a positive electrode layer slurry with good fluidity. The positive electrode layer slurry is applied to one side of the positive electrode active material so that the capacity is 5.0 mAh / cm 2 The cathode was obtained by applying the above-mentioned solution to one side of a 15 μm-thick Al foil having a 1 μm-thick carbon layer (composition: carbon black: CMC: SBR = 40:30:30 (vol%)) by a doctor blade method to obtain an area of 10.0 cm × 10.0 cm.
[0093] Negative electrode preparation The negative electrode active material was artificial graphite with an average particle size of 10.2 μm, and the electrolyte was a solution of 1M LiPF6 dissolved in a mixed solvent (EC:EMC = 25:75 vol). These were mixed and dispersed in a weight ratio of 60.0:40.0 to obtain a fluid negative electrode layer slurry. The negative electrode layer slurry was applied to the negative electrode active material on one side so that the capacity of the negative electrode active material on one side was 5.4 mAh / cm. 2 The solution was applied to one side of a 12 μm thick Cu foil by a doctor blade method to obtain a negative electrode having an area of 10.2 cm×10.2 cm.
[0094] Secondary battery production The tab-welded positive and negative electrodes were laminated together with a separator, sandwiched between aluminum laminates, and vacuum sealed. After charging and discharging at 0.2 CA, the battery was charged to SOC 70%, and aged at 55° C. for 24 hours to complete a secondary battery with a capacity of about 500 mAh. In the semi-solid positive electrode, the binder content was 0.01% by mass or less with respect to the total amount of the semi-solid positive electrode layer in the secondary battery completed in this embodiment. In the semi-solid negative electrode, the binder content was 0.01% by mass or less with respect to the total amount of the semi-solid negative electrode layer in the secondary battery completed in this embodiment.
[0095] (Example 2: Semi-solid electrode type secondary battery) In preparing the positive electrode, lithium cobalt oxide (LCO) having an average particle size of 15 μm was used as the positive electrode active material, carbon black having an average particle size of 2.8 μm was used as the conductive additive, and a solution obtained by dissolving 1M LiPF in a mixed solvent (EC:EMC=25:75 vol) as the electrolyte was mixed and dispersed in a weight ratio of 81:1:18 to obtain a positive electrode layer slurry having fluidity. A secondary battery was obtained in the same manner as in Example 1.
[0096] (Reference example: binder-bonded electrode type secondary battery) Positive electrode preparation Lithium cobalt oxide (LCO) with an average particle size of 15 μm was dispersed as a positive electrode active material, carbon black with an average particle size of 1 μm was dispersed as a conductive additive, and PVdF was dispersed as a binder in NMP in a weight ratio of 96:2:2 to obtain a positive electrode slurry. Then, a die coater was used to coat the active material on one side so that the capacity of the active material was 5.0 mAh / cm. 2 After applying the mixture to one side of an Al foil with a thickness of 15 μm and drying it, the mixture was compressed using a roll press machine so that the porosity was 18%, and then slit and cut to obtain a positive electrode of 10.0 cm × 10.0 cm.
[0097] Negative electrode preparation The negative electrode slurry was obtained by dispersing artificial graphite with an average particle size of 10 μm as the negative electrode active material, flake graphite with an average particle size of 3 μm as the conductive assistant, and CMC and SBR as the binder in a weight ratio of 96:1:3 (1.5 + 1.5) in water. Then, the active material capacity on one side was 5.4 mAh / cm using a die coater. 2 After coating and drying on one side of a 12 μm thick Cu foil so that the porosity was 23%, the foil was compressed using a roll press machine, and then slit and cut to obtain a negative electrode of 10.2 cm × 10.2 cm.
[0098] Secondary battery production The tab-welded positive and negative electrodes were laminated together with a separator between them, sandwiched between aluminum laminates, and a 1M electrolyte solution of LiPF6 dissolved in a mixed solvent (EC:EMC=25:75vol) was poured into the battery, which was then vacuum-impregnated and vacuum-sealed. After charging and discharging at 0.2CA, the battery was charged to SOC70% and aged at 55℃ for 24 hours to complete a secondary battery with a capacity of approximately 500mAh. In the positive electrode, the content of the binder was 2 mass % with respect to the total amount of the positive electrode layer in the completed secondary battery in this example.
[0099] (Comparative example 1: Semi-solid electrode type secondary battery) A secondary battery was obtained in the same manner as in Example 1, except that in producing the positive electrode, a normal Al foil having a thickness of 15 μm and no carbon layer was used as the Al foil to which the positive electrode layer slurry was applied.
[0100] (Comparative example 2: Semi-solid electrode type secondary battery) A secondary battery was obtained in the same manner as in Example 2, except that in producing the positive electrode, a normal Al foil having a thickness of 15 μm and no carbon layer was used as the Al foil to which the positive electrode layer slurry was applied.
[0101] (Electrode layer conductivity) The completed sample was subjected to volume resistivity measurement in the same manner as above, and the electrical conductivity of the electrode layer was measured by taking the reciprocal of the volume resistivity.
[0102] (Rate characteristics) The capacity retention rate X (0.2CA discharge capacity ratio) when discharging various completed secondary batteries at 25°C with 2CA was measured. ◎; 85% < X (best); 〇; 70% < X ≤ 85% (good); △; 50% < X ≤ 70% (no practical problem); ×; X ≤ 50% (practical problem exists).
[0103] (Degree of increase in rate characteristics by carbon layer) Example 1: (Capacity retention rate X of Example 1) / (Capacity retention rate X of Comparative Example 1) Example 2: (Capacity retention rate X of Example 2) / (Capacity retention rate X of Comparative Example 2)
[0104] Various evaluation levels and evaluation results are shown in Table 1.
[0105]
Table 1
[0106] The symbols in Table 1 are as follows. ※1: Mixing, coating, drying, pressing, slitting, cutting ※2: Tab welding, laminate production, liquid injection, vacuum impregnation, encapsulation, charge and discharge, aging ※3: Mixing, carbon layer formation, coating ※4: Tab welding, laminate production, encapsulation, charge and discharge, aging
[0107] In all examples and comparative examples, secondary batteries are manufactured in a very large area with a basis weight of 5.0 mAh / cm 2 Therefore, in Comparative Example 1 manufactured by a normal method including a binder, the resistance is high, resulting in low rate characteristics and cycle characteristics.
[0108] In Comparative Example 1, which uses a binder-free, fluid electrode, the secondary battery manufacturing process can be significantly simplified and the 2CA capacity retention rate can be improved, but the rate characteristics are poor because there is no carbon layer and the interface resistance with the Al foil is high.
[0109] In Example 1, in which an Al foil having a carbon layer was used, the rate characteristics were improved.
[0110] In Comparative Example 2, the amount of conductive additive in the positive electrode layer was further reduced, and the active material ratio (energy density) in the electrode layer was increased. However, the electrical conductivity of the electrode layer was below the threshold value of 1.0×10 -2 S / cm, the capacity retention rate is significantly lower than in Comparative Example 1.
[0111] In Example 2, the amount of conductive additive added was small, allowing the active material ratio in the composite to be high, and at the same time, an Al foil having a carbon layer was used, resulting in a high level of rate characteristics.
[0112] The rate characteristic of Example 1 is about 1.8 times that of Comparative Example 1. The rate characteristic of Example 2 is about 5.1 times that of Comparative Example 2. The conductivity of the electrode layer is 1.0×10 -2 When the resistance is lower than 1.0×10 S / cm, the resistance of the interface between the electrode layer and the current collector becomes the rate-limiting factor. -2 The effect of the carbon layer becomes greater in the region of conductivity such as S / cm. [Industrial Applicability]
[0113] The secondary battery of the present invention can be used in various fields where battery use or storage is anticipated. By way of example only, the secondary battery of the present invention can be used in electronics packaging fields. The secondary battery according to an embodiment of the present invention can also be used in the electrical, information, and communication fields in which mobile devices and the like are used (e.g., electrical and electronic devices fields including small electronic devices such as mobile phones, smartphones, smart watches, notebook computers, digital cameras, activity meters, arm computers, electronic paper, wearable devices, RFID tags, card-type electronic money, and smart watches, or mobile device fields), household and small industrial applications (e.g., power tools, golf carts, household, nursing care, and industrial robots), large industrial applications (e.g., forklifts, elevators, and port cranes), transportation systems (e.g., hybrid cars, electric cars, buses, trains, electrically assisted bicycles, and electric motorcycles), power system applications (e.g., various power generation, road conditioners, smart grids, and general household installation-type power storage systems), medical applications (medical devices such as earphones and hearing aids), pharmaceutical applications (medical management systems), IoT, and space and deep sea applications (e.g., space probes, submersible research vessels, and the like).
Claims
1. A semi-solid electrode layer including an electrode active material, a conductive assistant, and an electrolyte; a semi-solid electrode having a current collector; The semi-solid electrode is a secondary battery having a carbon layer between the semi-solid electrode layer and the current collector.
2. The carbon layer includes carbon black, 2. The secondary battery according to claim 1, wherein the carbon black content is 20% by volume or more and 60% by volume or less with respect to the total volume of the carbon layer.
3. 3. The secondary battery according to claim 1, wherein the carbon layer is a polymer layer having carbon black dispersed therein.
4. The conductivity of the semi-solid electrode layer is 1.0×10 -2 The secondary battery according to any one of claims 1 to 3, wherein the electrical conductivity is less than 1.0 S / cm.
5. The secondary battery according to any one of claims 1 to 4, wherein the secondary battery includes a semi-solid positive electrode and a semi-solid negative electrode, and at least one of the semi-solid positive electrode and the semi-solid negative electrode corresponds to the semi-solid electrode.
6. The secondary battery according to any one of claims 1 to 5, wherein the content of the electrode active material in the semi-solid electrode layer is 50 mass % or more and 90 mass % or less with respect to the total amount of the semi-solid electrode layer.
7. The secondary battery according to any one of claims 1 to 6, wherein the content of the conductive assistant in the semi-solid electrode layer is 0.1 mass % or more and 10 mass % or less with respect to the total amount of the semi-solid electrode layer.
8. The secondary battery according to any one of claims 1 to 7, wherein the content of the electrolyte in the semi-solid electrode layer is 30% by volume or more and 70% by volume or less with respect to the total amount of the semi-solid electrode layer.
9. 9. The secondary battery according to claim 1, wherein the carbon layer has a thickness of 0.1 μm or more and 10 μm or less.
10. The capacity per area of the semi-solid electrode is 4 mAh / cm 2 The secondary battery according to any one of claims 1 to 9.
11. The secondary battery according to any one of claims 1 to 10, wherein the semi-solid electrode layer is an electrode layer capable of absorbing and releasing lithium ions.
12. A method for producing the secondary battery according to any one of claims 1 to 11, comprising the following steps: a preparation step of mixing an electrode active material, a conductive assistant, and an electrolyte solution to prepare a slurry for an electrode layer; a carbon layer forming step of forming a carbon layer on the current collector; a coating step of coating a slurry for an electrode layer onto a current collector having a carbon layer to form an electrode; A lamination step of laminating the electrodes to form a laminate such that a separator is disposed between the electrodes; and an encapsulation step of encapsulating the laminate in an outer casing;
Citation Information
Patent Citations
Semi-solid electrodes with high speed capability
JP2016500465A